M-Track: progress tracking system for MOOC development / Harrinni Md Noor and Anealka Aziz - Md Noor, Harrinni; Aziz, Anealka (Universiti Teknologi MARA, 2020)
In 2014, the Ministry of Education initiated Massive Open Online Course (MOOC) pilot project at public universities in Malaysia. Universiti Teknologi MARA (UiTM) was selected among three public universities to develop the university’s own MOOC. This pilot project is one of the initiatives by the Malaysian government to support the ninth shift of Malaysia Education Blueprint 2015 – 2025 (Higher Education): Globalized Online Learning, which is introduced to achieve the desired outcomes set by the National e-Learning Policy (Dasar e-Pembelajaran Negara or DePAN). All MOOCs are now available on the Open Learning platform and offered throughout the year. It is a huge task indeed to manage and monitor simultaneous MOOC development in all UiTM faculties and state campuses. Thus, a tracking system to monitor the progress of MOOC development by lecturers called the MTrack System was designed. This paper explains how the system was developed and implemented. The system facilitates e-learning administrators to monitor the quality of MOOC at all 26 faculties and 12 UiTM campuses throughout Malaysia before there were offered to the public.The system can generate several types of report and this ensures the duration of MOOC development is adhered to. The target users of the system are the MOOC developers, MOOC Coordinators, MOOC Managers at the institution and anyone who wishes to develop MOOC.